2000
DOI: 10.1007/bf02492824
|View full text |Cite
|
Sign up to set email alerts
|

Detection, separation and analysis of α-amino acids by means of TLC using 4-diethylaminodiazabenzene-4′-isothiocyanate (DEABITC)

Abstract: Summary4-diethylaminodiazabenzene-4'-isothiocyanate (DEA-BITC) was synthetized and used to obtain thiohydantoin derivatives of 15 c~-amino acids (DEABTH-AMK). The coloured derivatives were separated by means of TLC on silica gel using various solvent systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Wawrzycki and Pyra () reported that derivatization of α ‐amino acids using 4‐(diethylamino)azobenzene‐4–‐phenyl isothiocyanate with DEABITC‐amino acids improves separation and facilitates detection of selected protein amino acids (in picomoles).…”
Section: Thin‐layer Chromatographymentioning
confidence: 99%
“…Wawrzycki and Pyra () reported that derivatization of α ‐amino acids using 4‐(diethylamino)azobenzene‐4–‐phenyl isothiocyanate with DEABITC‐amino acids improves separation and facilitates detection of selected protein amino acids (in picomoles).…”
Section: Thin‐layer Chromatographymentioning
confidence: 99%
“…The following are examples of analyses that include the formation of derivatives prior to TLC: the formation of fluorescent dansyl derivatives for determination of biogenic amines in red wine (79) and other foods (80) and of colored thiocarbamoyl derivatives of biogenic amines (81); the use of /?-benzoquinone for derivatization of 2-(methylamino)ethanol and other primary and secondary amines (82); the separation of /?-dimethylaminobenzaldehyde from p-dimethylaminocinnamaldehyde after derivatization with diphenylamine (83); determination of bisoprolol, labetalol, and propafenone as dabsyl derivatives in pharmaceutical preparations (84); and determination of the toxin fumonisin B-l in corn after immunoaffinity column cleanup and derivatization (85). In many cases, enantiomers have been resolved by TLC after the formation of derivatives, e.g., amino acids derivatized with l-fluoro-2,4-dinitrophenyl-5-L-alamne amide, and separated on RP plates (86).…”
Section: Derivatizationmentioning
confidence: 99%